Reading for Translation: Assessing Italian Fiction for British Publishers (1945–1968). - Sullam, Sara (Italianist, 2021)
Based on extensive archival research, this article focuses on the key role that the professional reading of foreign fiction had in the cultural mediation that takes place within publishing houses, arguing that readers' reports should be regarded as a form of specialised discourse on literature. It provides the first historical account of the cultural agency of the most important readers of Italian fiction working for British publishers with an interest in European literature in the period 1945–1968 (Jonathan Cape, Chatto & Windus, the Hogarth Press and The Bodley Head), assessing their educational and professional background and its influence on their critical perspective. To do this, it analyses three examples of professional reading, which concern the use of categories such as 'realism' and 'neorealism'; the consideration of genre and readability (with a focus on the translation of Natalia Ginzburg's Lessico famigliare); and the assessment of the political subtext of Vasco Pratolini's trilogy Una storia italiana.